2018
DOI: 10.1186/s12877-018-0805-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between occlusal force and falls among community-dwelling elderly in Japan: a cross-sectional correlative study

Abstract: BackgroundFalls may cause serious health conditions among older population. Fall-related physical factors are thought to be associated with occlusal conditions. However, few studies examined the relationship between occlusal force and falls. To identify the association between occlusal force and falls among community-dwelling elderly individuals in Japan, public health nurses conducted a cross-sectional descriptive study.MethodsWe performed extensive physical assessments of five items: maximum occlusal force, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…Three studies were retrieved through screening of previous systematic reviews. Altogether, there were 19 prospective studies [ 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] and 48 retrospective/case-control studies [ 18 , 19 , 21 , 23 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ...…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were retrieved through screening of previous systematic reviews. Altogether, there were 19 prospective studies [ 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] and 48 retrospective/case-control studies [ 18 , 19 , 21 , 23 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ...…”
Section: Resultsmentioning
confidence: 99%
“…As can be expected, hand grip strength was significantly lower in those individuals who could chew only soft or pureed food than in those individuals who could chew all kinds of food inferring that chewing ability was significantly related to hand grip strength after adjusting for the skeletal muscle mass, dentition status and background factors. In another study in Japan ( 40 ) with independent 159 community-dweller elderly aged 65 years old and above showed that maximum occlusal force was significantly correlated with the hand grip strength ( r = 0·382, P < 0·01). All these observed relationships between hand grip and oro-facial muscle strengths indicate possibilities of using hand gripping force by the carers as a non-invasive parameter to predict oral functions.…”
Section: Age-related Change In Measures Of Eating Capabilitymentioning
confidence: 96%
“…Complex oral function declines continuously with ageing and/or under the influences of disease and disability. Impaired oral function in later life is associated with degradation of oral health‐related quality of life 1 and with adverse general health outcomes such as malnutrition, frailty, functional disability and mortality 2‐8 …”
Section: Introductionmentioning
confidence: 99%
“…ROF, one of the seven clinical conditions for making a diagnosis of OHF, is closely associated with decreased masticatory function 11,12 and is certified to predict various adverse health outcomes of older people such as impaired nutritional status, reduced physical function, falls, frailty and functional disability, based on findings of several epidemiological studies 2‐8 . The JSG has recommended directly measuring the maximum occlusal force (MOF) in full dental arches by using pressure‐sensitive film as the primary test method to make a decision of ROF, and setting the threshold of MOF to 200 N, based on a previous study 13 that demonstrated an association between a low MOF (<200 N) and a low (<20 kg/m 2 ) or high (>25 kg/m 2 ) body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%